Kajian Sektor Unggulan Kota Padang di Provinsi Sumatera Barat Menggunakan Metode Location Quotient - Yenni Del Rosa; Nofri Yendra (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2023)
The purpose of the study was to identify the leading sectors as the leading sector in the city of Padang, the capital city of West Sumatra province, using the Location Quotient (LQ) method. The research data is in the form of secondary data, the type of ratio data, namely the GDP of the city of Padang in 2017-2021 according to the field of business (sector) based on the 2010 ADHB base year. The research population is 12 districts and 7 cities in the province of West Sumatra and the sample is the city of Padang determined by the purposive sampling technique. Processing and analyzing data using quantitative descriptive statistics. Based on the LQ analysis, the city of Padang in 2021 has 11 categories of business fields as its leading sectors as follows: 1) processing industry, 2) water supply, waste management and recycling, 3) transportation and warehousing, 4) information and communication, 5) services finance and insurance, 6) real estate, 7) corporate services, 8) government administration, defense and social security, 9) education services, 10) health services and social activities, 11) other services. Of the 11 categories of business fields, the company service sector has the highest LQ value as the leading sector with the largest contribution to GRDP. ABSTRAK Tujuan penelitian identifikasi sektor-sektor unggulan sebagai leading sector kota Padang ibu kota provinsi Sumatera Barat menggunakan metode Location Quotient (LQ). Data penelitian berupa data sekunder jenis data rasio yakni PDB kota Padang tahun 2017 – 2021 menurut lapangan usaha (sektor) berdasarkan ADHB tahun dasar 2010. Populasi penelitian 12 kabupaten dan 7 kota di provinsi Sumatera Barat serta sampelnya kota Padang ditentukan dengan teknik purposive sanpling. Pengolahan dan analisis data menggunakan statistik deskriptif kuantitatif. Berdasarkan analisis LQ kota Padang tahun 2021 mempunyai 11 kategori lapangan usaha sebagai sektor unggulannya sebagai berikut : 1) industri pengolahan, 2) pengadaan air, pengelolaan sampah limbah dan daur ulang, 3) transportasi dan pergudangan, 4) informasi dan komunikasi, 5) jasa keuangan dan asuransi, 6) real estate, 7) jasa perusahaan, 8) administrasi pemerintahan, pertahanan dan jaminan sosial, 9) jasa pendidikan, 10) jasa kesehatan dan kegiatan sosial, 11) jasa lainnya. Dari 11 kategori lapangan usaha tersebut sektor jasa perusahaan mempunyai nilai LQ paling tinggi sebagai sektor unggulan yang paling besar kontribusinya terhadap PDRB.